Experimental & Theoretical Analysis of Composite (Polyester & Silicon-Carbide) Cantilever Beam - Yousif, Yousif K. (Al-Khwarizmi Engineering Journal, 2012)
A cantilever beam is made from composite material which is consist of (matrix: polyester) and (particles: Silicon-Carbide) with different volume fraction of particles. A force is applied at the free end of beam with different values. The experimental maximum deflection of beam which occurs at the point of the applied load is recorded. The deflection and slope of beam are analyzed by using FEM modeling. MATLAB paltform is built to assemble the equations, vector and matrix of FEM and solving the unknown variables (deflection and slope) at each node. Also ANSYS platform is used to modeling beam in finite element and solve the problem. The numerical methods are used to compare the results with the theoretical and experimental data. A good agreement is observed between the above methods. The Increase in volume fraction of particles results in increasing the modulus of elasticity and decreasing the deflection of beam. An equation is suggested for modulus of elasticity as functions of volume fraction.